Endocannabinoid-mediated modulation of Gq/11 protein-coupled receptor signaling-induced vasoconstriction and hypertension. (5th March 2015) - Szekeres, Mária; Nádasy, György L.; Turu, Gábor; Soltész-Katona, Eszter; Benyó, Zoltán; Offermanns, Stefan; Ruisanchez, Éva; Szabó, Eszter; Takáts, Zoltán; Bátkai, Sándor; Tóth, Zsuzsanna E.; Hunyady, László
Highlights: Calcium signal generating GPCR agonist-induced vasoconstriction was enhanced in CB1 R-KO, compared to WT mice. Blockade of CB1 Rs enhanced calcium generating agonist-induced vasoconstriction. PGF2α -induced vasoconstriction was not modulated by CB1 Rs. Blockade of DAG lipase enhanced, blockade of MAG lipase attenuated AngII- vasoconstriction. Blockade of DAG lipase attenuated, but of MAG lipase augmented AngII-induced 2-AG level in VSMCs. Inhibition or genetic loss of CB1 R function augmented AngII-induced blood pressure rise in mice. Abstract: Activation of G protein-coupled receptors (GPCRs) can induce vasoconstriction via calcium signal-mediated and Rho-dependent pathways. Earlier reports have shown that diacylglycerol produced during calcium signal generation can be converted to an endocannabinoid, 2-arachidonoylglycerol (2-AG). Our aim was to provide evidence that GPCR signaling-induced 2-AG production and activation of vascular type1 cannabinoid receptors (CB1 R) is capable of reducing agonist-induced vasoconstriction and hypertension. Rat and mouse aortic rings were examined by myography. Vascular expression of CB1 R was demonstrated with immunohistochemistry. Rat aortic vascular smooth muscle cells (VSMCs) were cultured for calcium measurements and 2-AG-determination. Inhibition or genetic loss of CB1 Rs enhanced vasoconstriction induced by angiotensin II (AngII) or phenylephrine (Phe), but not by prostaglandin(PG)F2α . AngII-induced vasoconstriction was augmented by inhibition of diacylglycerol lipase (tetrahydrolipstatin) and was attenuated by inhibition of monoacylglycerol lipase (JZL184) suggesting a functionally relevant role for endogenously produced 2-AG. In Gαq/11 -deficient mice vasoconstriction was absent to AngII or Phe, which activate Gq/11 -coupled receptors, but was maintained in response to PGF2α . In VSMCs, AngII-stimulated 2-AG-formation was inhibited by tetrahydrolipstatin and potentiated by JZL184. CB1 R inhibition increased the sustained phase of AngII-induced calcium signal. Pharmacological or genetic loss of CB1 R function augmented AngII-induced blood pressure rise in mice. These data demonstrate that vasoconstrictor effect of GPCR agonists is attenuated via Gq/11 -mediated vascular endocannabinoid formation. Agonist-induced endocannabinoid-mediated CB1 R activation is a significant physiological modulator of vascular tone. Thus, the selective modulation of GPCR signaling-induced endocannabinoid release has a therapeutic potential in case of increased vascular tone and hypertension.